(untitled) - Association of Vietnamese historians; People's administrative committee of Hai Hung province (Hanoi, 1994)
This book introduce about the birth of Pho Hien, the scio-economic foundation of Pho Hien, its population structure and cultural life, the relations of Pho Hien with other areas in Viet Nam and with foreign countries, the process of decline of Pho Hien and the preservation of existing vestiges.
Keywords: Phố Hiến (Vietnam),Phố Hiến (Việt nam); History,Congresses,Lịch sử,Hội nghị